Transformative professional learning: an ecological approach to agency through critical reflection. Issue 4 (4th July 2017) - Jones, Marguerite; Charteris, Jennifer
Abstract: Within the global economy, education leverages social and economic improvement. Teachers are positioned as drivers and agents of compliance within change processes. Addressing this concern, we investigate intern teacher agency, as transformative professional learning, that occurs through a process of critical reflection. Critical reflection is conceived as an important element of teacher agency within the current political milieu. This article addresses the role of critical reflection in school-based intern teacher professional learning (PL). It is argued that intern teacher agency is inherent in transformative PL characterized through partnerships, which provide scope for decision-making and critical reflection.